RESILIENCE, CONFLICT-RELATED SEXUAL VIOLENCE AND TRANSITIONAL JUSTICE a social-ecological framing. - Clark, Janine N. (Janine Natalya) (ROUTLEDGE, 2022)
This interdisciplinary book constitutes the first major and comparative study of resilience focused on victims-/survivors of conflict-related sexual violence (CRSV). Locating resilience in the relationships and interactions between individuals and their social ecologies (including family, community, non-governmental organisations and the natural environment), the book develops its own conceptual framework based on the idea of connectivity. It applies the framework to its analysis of rich empirical data from Bosnia-Herzegovina, Colombia and Uganda, and it tells a set of stories about resilience through the contextual, dynamic and storied connectivities between individuals and their social ecologies. Ultimately, it utilises the three elements of the framework - namely, broken and ruptured connectivities, supportive and sustaining connectivities and new connectivities - to argue the case for developing the field of transitional justice in new social-ecological directions, and to explore what this might conceptually and practically entail. The book will particularly appeal to anyone with an interest in, or curiosity about, resilience, and to scholars, researchers and policy makers working on CRSV and/or transitional justice. The fact that resilience has received surprisingly little attention within existing literature on either CRSV or transitional justice accentuates the significance of this research and the originality of its conceptual and empirical contributions. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.